2013
DOI: 10.1111/ncmr.12004
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Role in Conflict Management: Female and Male Managers as Third Parties

Abstract: This study tested hypotheses drawn from the literature on gender, leadership, and conflict management about the outcomes facilitated by men and women in third party roles in dispute resolution in organizations. Data collected in association with an MBA teambuilding exercise showed that when women played third party roles in which they lacked authority over disputants, they were able to facilitate an outcome that was both acceptable to disputants and met organizational interests, more than men in these roles or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In this way, four additional empirical articles were found. Although some of them studied mainly managerial interventions (Benharda et al, 2013;Brett, Tinsley, Shapiro, & Okumura, 2007) or conflict management in general (Jameson, 2001;Morrill & Thomas, 1992), they all referred also to peer interventions in conflict. Finally, the entire search yielded a total of 12 empirical studies.…”
Section: Methods Literature Search Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…In this way, four additional empirical articles were found. Although some of them studied mainly managerial interventions (Benharda et al, 2013;Brett, Tinsley, Shapiro, & Okumura, 2007) or conflict management in general (Jameson, 2001;Morrill & Thomas, 1992), they all referred also to peer interventions in conflict. Finally, the entire search yielded a total of 12 empirical studies.…”
Section: Methods Literature Search Proceduresmentioning
confidence: 99%
“…Keashly and Newberry (1995) state disputants expect the peer Volume 11, Number 3, Pages 204-224 third party to have noticeable, however limited involvement in the predecision and outcome stages. Benharda et al (2013) found that supervisors acting as third party are perceived to have more power and influence, compared with peers, and tend to make more unilateral decisions to resolve the conflict. In Table 3 A Framework of Peacemaking Peacemaking happens.…”
Section: Outcomes Of Peacemakingmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the tendency for men (rather than women) to be judges, police, and bosses, it is also likely that a "culture of men" characterized the earliest tests of antecedents to procedural justice. This likely reduced scholars' ability to observe, also, the different ways in which male versus female managers intervene in employee disputes-as more recently theorized and found by Benharda, Brett, and Lempereur (2013).…”
Section: How Studying Dispute-resolving Led To Questions About What Cmentioning
confidence: 99%